Home and identity in nineteenth-century literary London - Robertson, Lisa C. (Edinburgh critical studies in Victorian culture., 2020)
This book brings together a range of new models for modern living that emerged in response to social and economic changes in nineteenth-century London, and the literature that gave expression to their novelty.